OP86 Understanding intervention acceptability: changing participant views over time and the importance of context. (2nd September 2017) - Morgan-Trimmer, S; Gregory, J; Townson, J; Channon, S; Chestnutt, I; Chadwick, B; Murphy, S; Hutchings, S
Abstract : Background: Acceptability is an important aspect of the quality of health interventions and also has implications for the feasibility of future implementation. Process evaluations of complex interventions often assess the acceptability of interventions through qualitative interviews with participants, addressing participants' experience of, satisfaction with and preferences for treatment/services received. Acceptability can be influenced by multiple aspects of an intervention and its context. This paper reflects on two process evaluations which produced complex findings on acceptability: the Delivering Early Care In Diabetes Evaluation (DECIDE) study, a trial of home vs. hospital care following a diagnosis of Type I diabetes (T1D) in children, and the Seal or Varnish (SoV) study which compared fluoride varnish and fissure sealant dental treatments to prevent caries in children. Methods: In the DECIDE study, semi-structured interviews with 11 (pairs of) parents and seven children were conducted 15–20 months post-diagnosis about their experience of hospital or home care immediately following diagnosis of T1D. In the SoV study, all children completed a 'smiley face' acceptability questionnaire immediately after treatment. In addition, paired semi-structured interviews were conducted with children at the beginning (50 children) and end (32 children) of the intervention, within a few days of receiving treatment. Interviews were divided evenly between trial arms; questions included experience of and acceptability of the interventions, diabetes management (DECIDE) and management of dental health (SoV). Results: In the DECIDE study, most interviewees wanted to be randomised to the 'home' arm initially but expressed a retrospective preference for whichever trial arm they had been in. This shift in preference may have been influenced by 'positive attitude' coping strategies adopted by families. In the SoV study, acceptability immediately post-treatment was related to which treatment was received, but acceptability in the week following treatment was strongly i nfluenced by wider aspects of treatment such as receiving a sticker and there was little difference in overall acceptability by trial arm. Perceptions of overall treatment may have been influenced by the intervention being delivered through a well-established, child-friendly dental service in a school setting. Conclusion: Both studies found that acceptability of an intervention can change over time, and indicated that participant restructuring of acceptability can be influenced by wider contextual factors of the intervention. Implications for future research are that the timing of data collection on acceptability may influence findings, and that acceptability (and implications for future implementation) should be interpreted in relation to intervention context.